ORAL ANTIDIABETICS AGENTS AVAILABLE IN INDIAN PHARMACEUTICAL MARKET: A PRICE VARIATION ANALYSIS - S THACKER, KUNTAL; R MISTRY, VIMESH; J KANANI, NEETA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: There are hundreds of brands in Indian markets for a single drug which is manufactured by various companies and thus leads to wide variation in prices for the same drug. Hence, we decide to evaluate the variation in price of different brands of the same drug available in Indian market. Methods: An analysis was done for comparing price variations among various drugs prescribed in diabetes mellitus. Indian Drug Review (IDR) (2019 Volume XXV Issue 4) and Current Index of Medical Specialties (CIMS) (July 2019–October 2019) were referred to know the maximum and minimum price in INR of drugs in all available strength and dosage forms being manufactured by different companies in India and percentage price variation was calculated. Results: Wide variation in the price of several brands of oral antidiabetics is found in Indian market. In single drug, highest price variation is found for glimepiride 1 mg tablet (1365.5%). In fixed-dose combinations (FDCs), highest price variation is found for glimepiride + metformin (2 mg + 500 mg) sustain release tablet (689.2%). Lowest price variation for FDCs was found for glimepiride + metformin (3 mg + 500 mg) tablet (4.8%). Furthermore, only few oral antidiabetic agents were included in the drug pricing control order 2013. Wide variation is seen in prices of brand and generic medicines. Conclusion: All the stakeholders should collectively make efforts to reduce price variation among the various brands so as to make them affordable and aim to improve the health status of the community.